Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Pegawai Dimediasi Kompetensi Digital Pada ILS Kabupaten Pringsewu - Wahit Nurrohman; Riswan Riswan; Oktavianur Oktavianur (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Improving employee performance has become a strategic issue for organizations, particularly in the era of work digitalization that demands rapid adaptation to the use of information technology. In the context of social service organizations, leadership effectiveness and employees’ digital competence readiness play a crucial role in supporting the achievement of organizational goals. This study aims to analyze the effect of transformational leadership on employee performance with digital competence as a mediating variable at Inisiasi Lampung Sehat (ILS), Pringsewu Regency. This study employed a quantitative approach with an explanatory research design. The research population consisted of all employees of ILS Pringsewu Regency, totaling 37 individuals, all of whom were included as the research sample using a total sampling technique. Data were collected through closed-ended questionnaires using a Likert scale and analyzed using multiple linear regression and path analysis with the assistance of SPSS software. The results indicate that transformational leadership has a positive and significant effect on employee performance, with a regression coefficient of 0.412 and a significance value of 0.002. Transformational leadership also has a positive and significant effect on employees’ digital competence, with a regression coefficient of 0.683 and a significance value of 0.000. Furthermore, digital competence is proven to have a positive and significant effect on employee performance, with a regression coefficient of 0.365 and a significance value of 0.006. Path analysis results show that digital competence partially mediates the effect of transformational leadership on employee performance, with the indirect effect being greater than the direct effect alone. These findings confirm that improving employee performance depends not only on the quality of transformational leadership but also on employees’ ability to master and utilize digital technology. Therefore, the integration of transformational leadership and digital competence development is a crucial strategy for sustainably enhancing employee performance.